Biocompatibility of the human mesenchymal stem cells with bovine bone tissue at the cellular level in vitro - Trebuňová, Marianna; Gromošová, Sylvia; Bačenková, Darina; Rosocha, Ján; Živčák, Jozef (Lékař a technika, 2018)
The purpose of this study was to investigate biocompatibility of the human mesenchymal stem cells with bovine bone tissue at the cellular level in vitro. Phenotypic analysis of cells was made by flow cytometry. Cells were grown on the bone for 12 days. Metabolic activity of cells was assessed with the MTS assay. The growth data were used to calculate the population doubling times. The scanning electron microscopy was used to verify the attachment of cells on the bone surface. The results were analyzed by using ANOVA test. Immunophenotypic characteristics were positive for CD105, CD90, CD73, and negative for CD34, CD45. The growth curves of stem cells of the 1st and the 2nd passages for both media, with and without, bovine bone were constructed. The increase of approximately 60% of the doubling time for mesenchymal cells co-cultivated with bovine bone tissue was observed for both passages in comparison with the control.Our study confirmed that mesenchymal stem cells are able to adhere to the bovine bone, even not being modified with bone-targeting elements. The proliferation rate and metabolic activity of cells co-cultivated with bone decrease in comparison with the control. Better survival was observed for cells of the 1st passage.
Keywords: tkáňové extrakty; průtoková cytometrie; Tissue Extracts; buněčné kultury; mezenchymální kmenové buňky; kosti a kostní tkáň; Humans; biokompatibilní materiály; testování materiálů; elektronová mikroskopie; Mesenchymal Stem Cells; Microscopy, Electron; kultivované buňky; Materials Testing; Biocompatible Materials; Flow Cytometry; Cells, Cultured; lidé; Cell Culture Techniques; Bone and Bones